Up-Regulation of Glycogen Synthesis and Degradation Enzyme Level Maintained Myocardial Glycogen in Huddling Brandt’s Voles Under Cool Environments - Xu, Jin-Hui; Wang, Zhe; Mou, Jun-Jie; Wang, Chuan-Li; Huang, Wei-Mei; Xue, Hui-Liang; Wu, Ming; Chen, Lei; Xu, Lai-Xiang (Frontiers in Physiology, 2021)
Small mammals exhibit limited glucose use and glycogen accumulation during hypothermia. Huddling is a highly evolved cooperative behavioral strategy in social mammals, allowing adaptation to environmental cooling. However, it is not clear whether this behavior affects the utilization of glycogen in cold environments. Here, we studied the effects of huddling on myocardial glycogen content in Brandt’s voles (Lasiopodomys brandtii) under a mild cold environment (15 °C). Results showed that (1) Compared to the control (22 °C) group (CON), the number of glycogenosomes more than tripled in the cool separated group (CS) in both males and females; whereas the number of glycogenosomes increased in females but was maintained in males in the cool huddling group (CH). (2) Glycogen synthase (GS) activity in the CS group remained unchanged, whereas glycogen phosphorylase (GYPL) activity decreased, which mediated the accumulation of glycogen content of the CS group. (3) Both GS and GYPL activity increased which may contribute to the stability of glycogen content in CH group. (4) The expression levels of glucose transporters GLUT1 and GLUT4 increased in the CS group, accompanied by an increase in glucose metabolism. These results indicate that the reduced glycogen decomposition level and enhanced glucose transport may lead to an increase in myocardial glycogen content of the separated voles under cool environment; while the up-regulation of glycogen synthesis and decomposition level maintained myocardial glycogen content in the huddling vole.